Is electroconvulsive therapy safe for patient with very low BMI? a case report - Loo, JL; Farah Deena Abdul Samad,; Hatta Sidi, (Fakulti Perubatan, UKM, 2016)
A case of rapid stabilization using electroconvulsive therapy (ECT) for a major depressive disordered (MDD) patient with life-threatening low body mass index (BMI) is reported. This case report focuses on a 55-year-old Malay housewife with underlying hyperthyroidism in a euthyroid state who presented with MDD with mood congruent psychotic features, which were precipitated by the death of her husband. Her BMI was only 11 kg/m2 due to severe anorexia, and she was highly suicidal. Peripheral total parenteral nutrition was started and ECT was commenced for rapid stabilization on top of tablet escitalopram 15 mg nocte. Full remission was achieved after nine ECTs and steady healthy weight gain was achieved throughout admission. The patient was discharged at BMI of 13 kg/m2 with good appetite. ECT was safe for very low BMI MDD patient.